2014
DOI: 10.4103/1673-5374.128218
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Angelica sinensis alleviate neuronal cell injury caused by oxidative stress

Abstract: Angelica sinensis has antioxidative and neuroprotective effects. In the present study, we aimed to determine the neuroprotective effect of polysaccharides isolated from Angelica sinensis. In a preliminary experiment, Angelica sinensis polysaccharides not only protected PC12 neuronal cells from H2O2-induced cytotoxicity, but also reduced apoptosis and intracellular reactive oxygen species levels, and increased the mitochondrial membrane potential induced by H2O2 treatment. In a rat model of local cerebral ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“… 27 ASP exerts neuroprotective effects by limiting cerebral ischaemia/reperfusion injury, 28 increasing microvessel number, and improving blood flow after cerebral ischaemia. 29 The antioxidant activity of ASP has been tested in in vivo and in vitro experimental models. Zhuang et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 27 ASP exerts neuroprotective effects by limiting cerebral ischaemia/reperfusion injury, 28 increasing microvessel number, and improving blood flow after cerebral ischaemia. 29 The antioxidant activity of ASP has been tested in in vivo and in vitro experimental models. Zhuang et al.…”
Section: Discussionmentioning
confidence: 99%
“…showed that ASP attenuated an H 2 O 2 -induced increase in apoptosis and ROS levels in PC12 neuronal cells, and enhanced the activity of antioxidant enzymes in cortical tissues of rats with focal cerebral ischaemia. 29 Additionally, ASP treatment reduced the senescence of endothelial progenitor cells by relieving OS. 31 However, the effect of ASP on oxidative injury in cardiomyocytes and mechanisms underlying this effect are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been used as health food for women's care in Europe and America [ 14 ]. Recent studies have shown that polysaccharides, among other products, from A. sinensis have antioxidant and neuroprotective functions [ 15 ], but similar activities have not been addressed on peptides from A. sinensis . Using the nematode Caenorhabditis elegans , a powerful model organism for aging and neurobiology studies, we investigated the antioxidant and anti-aging activities of peptide preparations derived from A. sinensis roots, including their effect on oxidative survival, ROS levels, antioxidant enzyme activities, lipid peroxidation product content, age pigments content, and lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, polysaccharides isolated from functional and medicinal foods as well as from common foods have drawn great attention in antioxidant studies. Here, we attempt to summarize recent studies of antioxidant polysaccharides from food resources, including vegetables, fruits, cereals, beans, mushrooms, tea, milk products and meat ( Table 1 ) [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Reduction Of Oxidative Stress By Food-derived Polysaccharmentioning
confidence: 99%